Microbiota profile in organs of the horseflies (Diptera: Tabanidae) in Northeastern China - Qiu, Hong-Yu; Lv, Qing-Bo; Wang, Chun-Ren; Ju, Hao; Luo, Chun-Feng; Liu, Shun-Shuai; Na, Mu-Han; Chang, Qiao-Cheng; Jiang, Jia-Fu (Frontiers in Microbiology, 2024)
Tabanids, commonly known as horseflies and belonging to the family Tabanidae, are blood-feeding arthropods (BFA) found worldwide. They are known for their ability to mechanically and biologically transmit various animal pathogens. Tabanids are potential vectors for diseases such as Francisella tularensis, Anaplasma marginale, Theileria spp., and contributors to lumpy skin diseases.Despite their involvement in common BFA studies, tabanids have not been extensively explored in microbiome research. In this study,the microbiota structure and composition in various organs of four distinct genera of tabanids: Atylotus, Haematopota, Tabanus, and Hybomitra were examined. Highthroughput sequencing of the bacterial 16S rRNA gene was performed to gain insights into the microbial communities associated with the different tabanid species. Result display that microbiota composition and diversity, including Firmicutes, Proteobacteria, and Bacteroidetes, varied significantly among the different organs, with the ovaries exhibiting significantly higher diversity.Apart from the Haematopota genus, Tenericutes were enriched in the midgut of other tabanid species, whereas the Malpighian tubules exhibited a higher abundance of Bacteroides. Notably, the ovarian microbiota structure was conserved among the four tabanid species, indicating its potential association with reproductive development. Evaluation of the potential pathogen risk revealed putative pathogens in over 100 genera associated with these tabanid commensal organisms. Twenty genera were annotated as zoonotic agents with a high abundance of Citrobacter and Brucella, highlighting the presence of this important group of zoonotic pathogens. Functional predictions of vector-microbiota interactions indicate that microbiota significantly affects vector biological traits and can influence pathogen transmission via direct interactions or by regulating host immunity and nutrition.For the first time, the distribution characteristics and functions of four genera of horsefly microbiota were analyzed, revealing the presence of multiple potential pathogenic microorganisms.These findings provide valuable insights for future research and the development of symbiotic-based strategies to control insect-borne diseases among tabanids..